2006
DOI: 10.1007/s00441-006-0318-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of neuropeptides in the primary olfactory center of the heliothine moth Heliothis virescens

Abstract: Neuropeptides are a diverse widespread class of signaling substances in the nervous system. As a basis for the analysis of peptidergic neurotransmission in the insect olfactory system, we have studied the distribution of neuropeptides in the antennal lobe of the moth Heliothis virescens. Immunocytochemical experiments with antisera recognizing A-type allatostatins (AST-As), Manduca sexta allatotropin (Mas-AT), FMRFamide-related peptides (FaRPs), and tachykinin-related peptides (TKRPs) have shown that members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 60 publications
8
57
0
Order By: Relevance
“…A recent study on the distribution of various neuropeptides in the adult AL of the noctuid moth Heliothis virescens revealed about the same numbers of neuropeptide immunoreactive neurons in the lateral cell group for the same three antisera used in the various M. sexta studies (Mas-AT: *87; AST-A: *47; RFamide: *64; Berg et al, 2007). Double immunostainings with antisera against Mas-AT and AST-A or RFamide antisera using the same method as in the current study, revealed a similar number of neurons which colocalize Mas-AT and AST-A (*32) but only about half of the number which colocalize Mas-AT and RFamide (*15) immunoreactivity.…”
Section: Colocalization Of Mas-at With Gaba Rfamides and A-type Allmentioning
confidence: 93%
See 3 more Smart Citations
“…A recent study on the distribution of various neuropeptides in the adult AL of the noctuid moth Heliothis virescens revealed about the same numbers of neuropeptide immunoreactive neurons in the lateral cell group for the same three antisera used in the various M. sexta studies (Mas-AT: *87; AST-A: *47; RFamide: *64; Berg et al, 2007). Double immunostainings with antisera against Mas-AT and AST-A or RFamide antisera using the same method as in the current study, revealed a similar number of neurons which colocalize Mas-AT and AST-A (*32) but only about half of the number which colocalize Mas-AT and RFamide (*15) immunoreactivity.…”
Section: Colocalization Of Mas-at With Gaba Rfamides and A-type Allmentioning
confidence: 93%
“…Direct profiling of ALs of several insects including M. sexta, Heliothis virescens, Apis mellifera, and the beetle Tribolium castaneum by MALDI-TOF mass spectrometry suggests about 40-50 different neuropeptides in the ALs of each of these species (Berg et al, 2007;Utz et al, 2007;and unpublished). Neuropeptides have often been considered as cotransmitters that are released in concert with a principal transmitter (Vilim et al, 2000;Nässel, 2002).…”
Section: Possible Roles Of Mas-at and Other Neuropeptides During Al Dmentioning
confidence: 94%
See 2 more Smart Citations
“…Bicker, 1999;Homberg, 2002;Schachtner et al, 2005;Berg et al, 2009;Fusca et al, 2015). In addition AL neurons contain neuromediators like biogenic amines, gaseous signaling molecules like NO and a large variety of neuropeptides suggesting important involvement for proper olfactory behavior (e.g.…”
mentioning
confidence: 99%